2007
DOI: 10.1111/j.1365-2842.2007.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical and chemical methods on denture biofilm accumulation

Abstract: The aim of this study was to quantify biofilm on the internal surface of upper complete dentures following six possible cleansing methods. Thirty-six edentulous subjects were submitted to a time-series trial and dentures were cleansed according to six methods: (i) rinsing with water; (ii) soaking in an alkaline peroxide solution (Bonyplus); (iii) brushing with dentifrice (Dentu-Creme) and soft Johnson and Johnson's toothbrush; (iv) combination between soaking and brushing according to methods 2 and 3; (v) brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
207
3
57

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(269 citation statements)
references
References 28 publications
2
207
3
57
Order By: Relevance
“…Several agents are indicated for denture biofilm removal, classified into mechanical and chemical agents (1). Cleaning by chemical method consists in immersing the denture in solutions with solvent, detergent, antibacterial and antifungal actions, and such solutions can be employed alone or in association with brushing or ultrasonic devices (2,3). There are two main classes of immersion denture cleansers: NaOCl and alkaline peroxides (4).…”
Section: Introductionmentioning
confidence: 99%
“…Several agents are indicated for denture biofilm removal, classified into mechanical and chemical agents (1). Cleaning by chemical method consists in immersing the denture in solutions with solvent, detergent, antibacterial and antifungal actions, and such solutions can be employed alone or in association with brushing or ultrasonic devices (2,3). There are two main classes of immersion denture cleansers: NaOCl and alkaline peroxides (4).…”
Section: Introductionmentioning
confidence: 99%
“…6 Various denture hygiene procedures are mentioned in the literature and these can be divided into mechanical and chemical methods. [7][8] A study conducted by Abhishek Apratim et al concluded that most common method of cleaning was mechanical either with water or with soap. 9 Frequency of cleaning with cleansing solutions was very low.…”
Section: Introductionmentioning
confidence: 99%
“…However, many elderly subjects are affected by diseases that limit their manual ability [3][4] , thus requiring complementation of the mechanical cleaning with chemical substances in order to avoid the accumulation of dental microbial plaque on the oral mucosa membrane and on the surfaces of dentures, what may lead to the development of several diseases, such as candidiasis [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…An effective alternative method that has been currently used is microwave irradiation to fight several diseases and eliminate colonization by Candida albicans 4,[8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%